PENGARUH KOMPETENSI GURU, PERHATIAN ORANG TUA, DAN TEMAN SEBAYA TERHADAP MOTIVASI BELAJAR QUR’AN HADIS - muhammad gaffarur rozi (Murabby: Jurnal Pendidikan Islam, 2021)
This study aims to determine the effect of teacher competence, attention of parents, and peers on the motivation to learn Qur'anic Hadiths of class X Madrasah Aliyah in East Lombok Regency. The research method used is a quantitative approach with descriptive correlational type. The study population was all students of class X Madrasah Aliyah in East Lombok with a cluster random sampling technique. The results showed: first, there was a positive and significant influence of teacher competence on student learning motivation, with a correlation number rx_1y = 0.405 and a coefficient of determination of R ^ 2 X_1Y = 0.164. second, there is a positive and significant influence of parental attention on student motivation, with a correlation number of rx_2y = 0.387 and a coefficient of determination of R ^ 2 X_2Y = 0.150. third, there is a positive and significant influence of peers on student learning motivation, with the correlation number rx_3y = 0.326 and the coefficient of determination of R ^ 2 X_3Y = 0.106; fourth, there is a positive and significant influence on teacher competence, the attention of parents and peers together on the learning motivation of class X students in the subject of the Qur'an Hadith Madarasah Aliyah in East Lombok Regency, with a correlation rate of rxy (1,2, 3) = 0.513 and the coefficient of determination is R ^ 2 xy (1,2,3) = 0.263.